Hakikat Putusan Pencabutan Hak Dipilih Terpidana Korupsi Politik dalam Perspektif Hak Asasi Manusia - Handoko Alfiantoro (University of Jember, 2016)
Corruption is one type of dangerous unconventional crime that need special ways in their handling patterns. One important instrument in the context of law enforcement against criminal acts of corruption is the existence of additional crimes in the form of revocation of certain rights in terms of the right to vote and be elected in elections held based on general rules. Revocation of political rights for convicted political corruption is a form of state intervention against restrictions on human rights in the right to be elected in elections. However, this becomes a problem in the perspective of human rights when the revocation of political rights is done permanently not within a certain period. This article has been prepared using a normative juridical research method through a statute approach, a comparative approach, and a conceptual approach, which aims to critically examine the nature of the Decision on the Revocation of the Selected Rights of Convicted Political Corruption in the Perspective of Human Rights. KEYWORDS: Revocation of Selected Rights, Human Rights, Political Corruption.